Modern hydro-energy problems in Central Asia - K. S. Zakharova (Проблемы постсоветского пространства, 2018)
One of the most complex problems for Central Asia is scarcity of fresh water and related transboundary water-sharing. The current situation is the result of countries` economic policy, lack of regional engagement on water use, global climate change, population growth and increased consumption of water resources, what has already influenced on reducing water availability.Feature of Central Asian drainage system is extremely uneven distribution of water resources not only throughout the region, but also throughout each country, what does not let republics take full advantage of water resources in its ensuring of the national interests. The major water sources of the region located on the territory of two countries as Kyrgyz Republic and Republic of Tajikistan, what causes difficulties in relations of these countries with Republic of Kazakhstan, Turkmenistan and Republic of Uzbekistan. Furthermore, situation is compounded by different approaches of Central Asian countries to water use.Since the early 1990s, water issues became a factor of regional security. The potential of conflict in current mechanisms for water distribution is notably high, that is why water issues one of the priorities on the list of Central Asian problems and requires constant monitoring. Despite many discussion and attempts to resolve regional water problem, the sides have not come to an agreement. Involvement of other countries and international organizations in development of water problem solution has not been successful.With the election of a new President of Republic of Uzbekistan, there have been a warming of relations in the region and trend towards joint policy-making with respect to Central Asian development. That could have a positive impact on the situation with hydro-energy resources.